Animals, foods, and household items—oh my! Evidence of 24-30-month-old children’s increasing flexibility in word learning from naturalistic data - Russell Emily E. (Sciendo, 2021)
At 18 months of age, children frequently generalize (and overgeneralize) novel objects’ labels by shape (Landau et al., 1988). However, data from laboratory studies using ostensive word-learning paradigms indicate that, by three years of age, children generalize the labels of novel objects depending on the objects’ perceptual characteristics and taxonomy (Lavin & Hall, 2001; Jones et al., 1991). The current study sought to document this shift in children’s word-learning strategies using naturalistic data. We tracked children’s vocabularies over a six-month period of time (between 24-30 months of age) and classified their known words according to perceptual organization of the object categories to which they refer (e.g., shape-based, material-based). Children’s vocabulary sizes and rates of growth varied in meaningful ways between types of object categories and between the superordinate categories (e.g., animals, toys) to which the object categories belong. Findings carry implications for two popular accounts of vocabulary acquisition.